Waswas in the quran: Insights and strategies for overcoming spiritual distractions - Busari Afeez Babatunde; Ibnu Fitrianto; Aris Munandar; Nasih Muhammad (Yayasan Azhar Amanaa Yogyakarta, 2025)
The concept of waswas is a recurring theme in Islamic teachings, particularly in the Quran, where it is depicted as a subtle yet powerful tool used by Shaytan to mislead believers. This study explores the nature of waswas as described in the Quran, its psychological and spiritual implications, and the strategies prescribed in Islamic teachings to combat it. By analyzing key Quranic verses and interpretations from classical and contemporary scholars, this paper aims to provide a deeper understanding of waswas and its effects on faith, decision-making, and mental well-being. The study further highlights practical approaches, including supplications (du'a), remembrance of Allah (dhikr), and adherence to Islamic principles, to resist and overcome satanic whisperings. Ultimately, this research seeks to offer a comprehensive perspective on maintaining spiritual resilience in the face of these challenges. By understanding the nature of waswas and implementing Quranic guidance, believers can cultivate greater spiritual resilience and maintain focus in their religious and personal lives. This paper aims to equip readers with a deeper understanding of waswas and effective methods to combat it.